Studi Awal Pemanfaatan Limbah Fly Ash dan Bottom Ash Sebagai Material Alternatif dalam Bidang Konstruksi - Buyung Mantap (Journal of Science, Technology, and Innovation, 2025)
The utilization of fly ash and bottom ash as alternative materials in construction has expanded in response to sustainability imperatives and increasing volumes of industrial by-products. This study consolidates and critically organizes existing scientific knowledge to clarify the relationships between material characteristics, mechanical performance, and sustainability considerations associated with fly ash and bottom ash. The analysis demonstrates that their mechanical behavior is highly dependent on physical–chemical properties, mixture design, and environmental context, indicating that performance cannot be generalized across applications. Although environmental benefits are frequently emphasized, sustainability is often framed in a simplified manner, with limited integration of life cycle impacts, social dimensions, and institutional constraints. The findings also reveal methodological inconsistencies and conceptual gaps that hinder knowledge transfer and practical implementation. By structuring dispersed evidence into a coherent analytical perspective, this study contributes to a clearer understanding of the conditions under which fly ash and bottom ash can be responsibly utilized. The outcomes provide a foundation for guiding future experimental development and supporting more informed decision-making in sustainable construction systems.